POLA PENYEBARAN GAS NO 2 DI UDARA AMBIEN KAWASAN UTARA KOTA SEMARANG PADA MUSIM KEMARAU MENGGUNAKAN PROGRAM ISCST3 - Hadiwododo, Mochtar; Huboyo, Haryono Setiyo (Universitas Diponegoro, 2006)
North district of Semarang City is an area characterized by dense population, congested transportation, and high industry activities. Urban activities in this area are predicted produce enourmous pollutant one of them is NO 2 . This gas is hazardous for human health, and can cause death even that concentration exceed standard level 150 µgr/m3. Inventory emission is used to identify sources that produce NO 2 gas and quatify the concentration. ISCST3 program was used as a tool to recapitulate the dispersion of NO 2 gas in ambient from it sources to the potent receptor. Combinated with Surfer program, it result were easily be visualized trough NOx isopleth contour overlaid to land used map. The result of this observation showed that total emission of NO 2 gas in area observation is 0,001445 ton/year where is transportation contributes 91,68 %, followed by industry 8,31 %, and domestic 0,01 %. Dispersion pattern of NO 2 gas in ambient is mainly affected by calm condition of wind making NO 2 gas is concentrated in 3 regions i.e Pindrikan Kidul, Peterongan, and Tambakrejo.